2014
DOI: 10.1071/an12314
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH decline rate on the meat and eating quality of beef carcasses

Abstract: Abstract. An experiment was undertaken to examine the effect of rapid pH fall at a high muscle temperature on meat and eating quality of two beef cuts (striploin and cube roll). From 115 beef steer carcasses of which the right side of each carcass was subjected to electrical stimulation, 25 carcasses which exhibited the largest difference in the rate of pH fall in the M. longissimus between sides were selected for subsequent sampling. All of the stimulated sides missed the 'ideal' pH/ temperature window (defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 29 publications
3
42
1
4
Order By: Relevance
“…The authors emphasised the fact that inefficient stimulation may lead to tougher meat and higher drip loss, probably through higher levels of protein denaturation as muscle spends more time in higher temperature zones during the course of rigor. Likewise, muscle of heavy carcasses that is not stimulated and chilled slowly pre-rigor will also be exposed to unfavourable conditions for a longer time, as also mentioned by Hopkins et al (2014). Despite this convincing argument, it is difficult to understand why Warner et al (2014c), supported by other studies (Devine et al 1999;Thompson 2001a, 2001b), reported a limited ageing potential for cuts above the MSA pH-temperature window.…”
Section: Application Of Electrical Stimulation and Contradictory Resmentioning
confidence: 67%
See 4 more Smart Citations
“…The authors emphasised the fact that inefficient stimulation may lead to tougher meat and higher drip loss, probably through higher levels of protein denaturation as muscle spends more time in higher temperature zones during the course of rigor. Likewise, muscle of heavy carcasses that is not stimulated and chilled slowly pre-rigor will also be exposed to unfavourable conditions for a longer time, as also mentioned by Hopkins et al (2014). Despite this convincing argument, it is difficult to understand why Warner et al (2014c), supported by other studies (Devine et al 1999;Thompson 2001a, 2001b), reported a limited ageing potential for cuts above the MSA pH-temperature window.…”
Section: Application Of Electrical Stimulation and Contradictory Resmentioning
confidence: 67%
“…At the latter point, high rigor temperature cuts reached their maximum tenderness level. In the study of Hopkins et al (2014), tenderness values of high rigor temperature cuts created by ES ran parallel to those of cuts that were within the pH-temperature window (non-stimulated carcasses, NES) from slaughter to 14 days, and differentiation after that was probably not likely to happen with ageing taking place at 0À1 C, although this was not confirmed. Furthermore, ES muscles recorded no initial advantage (1 day) as would have been expected (Thomson et al 2008;Kim et al 2012;Warner et al 2014a).…”
Section: Application Of Electrical Stimulation and Contradictory Resmentioning
confidence: 99%
See 3 more Smart Citations